Real time enterprise as a platform of support management systems - Jerzy Kisielnicki; Marek Michal Markowski (Foundations of Management, 2021)
The current, fast market changes require enterprises to dynamically adapt the way they conduct their business. This poses many challenges for information technology. Market requirements for immediate response to business changes became the basis of the idea of a real-time information processing (RTE) company. RTE provides real-time information to employees and business partners. Integrated IT systems supporting management constitute a common platform - the foundation of a real-time enterprise. The aim of the article is to present the basic problems of building an IT system that is the basis of a real-time information processing (RTE) company. It is a summary of our work on this type of system. The article justifies the thesis about the need to build a system for the RTE's requirements and the conditions of its implementation. Such a system is designed to provide employees and business partners with the information they need in real time. The use of integrated systems such as ERP, CRM, SCM, and so on provides the ability to implement the main business processes of a real-time enterprise. The article presents both literature analysis and the characteristics of own work on designing IT systems for RTE. Particular attention was paid to the analysis
Keywords: L83; L23; 650; RTE; Real Time Enterprise; computer systems integration; business processes; IT design determinant; IT systems platform